2017
DOI: 10.1021/acs.est.6b05887
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Integrons as the Carrier of Antibiotic Resistance Genes in Natural and Man-Made Environments

Abstract: Class 1 integrase intI1 has been considered as a good proxy for anthropogenic pollution because of being linked to genes conferring resistance to antibiotics. The gene cassettes of class 1 integrons could carry diverse antibiotic resistance genes (ARGs) and conduct horizontal gene transfer among microorganisms. The present study applied high-throughput sequencing technique combined with an intI1 database and genome assembly to quantify the abundance of intI1 in 64 environmental samples from 8 ecosystems, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
94
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(110 citation statements)
references
References 40 publications
13
94
1
2
Order By: Relevance
“…It is known that AMR and MDR in E. coli are acquired by the transfer of mobile genetic elements, such as plasmids, transposons and integrons [15, 18, 20]. In the present study, of the 178 E. coli isolates, class 1 integrons were detected (Fig 2) in 175 (98.3%), and class 2 in 5 (2.8%).…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…It is known that AMR and MDR in E. coli are acquired by the transfer of mobile genetic elements, such as plasmids, transposons and integrons [15, 18, 20]. In the present study, of the 178 E. coli isolates, class 1 integrons were detected (Fig 2) in 175 (98.3%), and class 2 in 5 (2.8%).…”
Section: Resultssupporting
confidence: 48%
“…Considering that all the isolates were MDR, the detected high prevalence of class 1 integron is not surprising and compares with a previous study that reported that MDR phenotypes were observed in 96.8% of the integron-positive isolates [35]. These rates portend serious public health risks as it is known that class 1 integron could carry diverse antibiotic resistance genes (ARGs) and conduct horizontal gene transfer among microorganisms [20].…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Conversion by the non-sterile larvae was the most effective treatment to attenuate ARGs, followed by conversion by sterile larvae. For the integrin genes, which function to facilitate ARG gene flow (Ma et al, 2017), the absolute abundance of intI 1 and intI 2 was also significantly decreased in both the non-sterile and sterile larvae treatments, but occurred more slowly in the controls. The results demonstrated that BSF larvae effectively reduced the abundance of ARGs and integrin genes.…”
Section: Absolute Abundance Changes In Target Genesmentioning
confidence: 95%
“…The study also identi ed the presence of MGEs, including three important integrons and one transposon [45,46] (Fig. 3), which play important roles in the transfer and acquisition of ARGs in various microorganisms via HGT.…”
Section: Occurrence and Abundances Of Mgesmentioning
confidence: 99%